Increasing predominance of G8P[8] species A rotaviruses in children admitted to hospital with acute gastroenteritis in Thailand, 2010-2013 - Arpaporn Yodmeeklin (2018)
© 2018, Springer-Verlag GmbH Austria, part of Springer Nature. Rotavirus A is a well-known etiological cause of acute gastroenteritis in infants and young children worldwide. In this study, we investigated the prevalence and distribution of RVA genotypes circulating in children with acute gastroenteritis in Thailand from 2010 to 2013. A total of 1,032 fecal specimens were collected from children with an age range from neonatal to 15 years of age and tested for RVA by RT-PCR. Of these, 184 (17.8%) were positive for RVA. The highest detection rate of RVA was found in children aged between 12 and 24 months. The G1P[8] genotype was identified as the most dominant genotype (57.6%), followed by G2P[4] (12.5%), G8P[8] (10.4%), G9P[8] (7.1%), G3P[8] (4.9%), G1P[4] (2.2%), G2P[8] (1.7%), and mixed-infections of G1 and G3 in combination with P[8] (0.5%). In addition, the uncommon human rotavirus strains G4P[6] (1.1%), G9P[19] (0.5%), G12P[4] (0.5%), and G12P[6] (0.5%) were also detected in this study. Interestingly, the unusual G8P[8] strains were detected at a relatively high frequency, and phylogenetic analysis revealed that these G8 strains were genetically closely related to bovine and bovine-like human G8 rotavirus strains reported previously from Thailand, Japan, Vietnam, India and Taiwan. These G8P[8] strains displayed the DS-1-like genotype constellation of G8-P[8]-I2-R2-C2-M2-A2-N2-T2-E2-H2 (in the order VP7-VP4-VP6-VP1-VP2-VP3-NSP1-NSP2-NSP3-NSP4-NSP5/6, respectively). Overall, the data indicated a high degree of diversity of RVA genotypes, with the emergence of several uncommon RVA strains in children with acute gastroenteritis in Thailand.